Effects of light-load vs. heavy-load jump squats as priming activities in Olympic female rugby sevens players - Loturco, I.; Zmijewski, P.; Mercer, V. P.; Ramos, M. S.; Betelli, M. T.; Arenhart, I.; Moura, T. B. M. A.; Pereira, L. A. (Biology of Sport, 2025)
Priming activities have been widely used by coaches as a strategy to enhance physical performance within short periods (6-24 hours) before sport-specific training sessions and competitions. In this crossover study, we examined and compared the effects of two different priming schemes on the speed-power performance of female rugby sevens players. One hour after completing a standardized warm-up and a series of measurements including loaded and unloaded jumps and speed-related tests, twenty Olympic female rugby sevens players performed, one week apart, 6 sets of 6 reps of jump-squats (JS) at either 40% (light-load; LL) or 80% 1RM (heavy-load; HL). Countermovement jump height increased significantly 6-h after both loading conditions (ES=0.50 and 0.34, for LL and HL, respectively; P < .001), with no changes observed at the 24-h time-point. JS peak velocity improved significantly after 24-h compared to the pre-testing, but solely for the lighter loading intensity (i.e., JS at 40%1RM; ES=0.63; P=0.006). 40-m sprinting speed increased significantly at the 6-h timepoint for both LL (ES=0.20; P=0.001) and HL (ES=0.18; P=0.004), without showing significant changes in the following 24-h. COD speed improved significantly after both priming schemes at the 6- and 24-h time points, regardless of the loading condition (P = 0.027 for the main effect of time). No time×loading condition interaction was detected for any variable assessed, with P-values ranging from 0.111 to 0.953. Importantly, the rate of perceived exertion was significantly higher after the priming protocol at the HL condition (P=0.02), which may lead to increased levels of fatigue and decreased performance in subsequent activities. Elite coaches from rugby sevens (and other team sports) should strongly consider these findings when programming priming training sessions in the periods preceding more intensive training sessions and official matches due to the potential disadvantages associated with the use of heavier loads (i.e., = 80% 1RM).